2013
DOI: 10.2219/rtriqr.54.112
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Dynamic Simulation of a Train Set Running on Ballasted Track after Derailment

Abstract: The dynamic motion of a train set will be affected by the change in running resistance as the wheels run over sleepers or ballast. It is therefore important to determine the motion of vehicles in such situations both experimentally and theoretically. A 1 to 10 scale model vehicle was used to perform running tests during which the vehicle was made to collide against model iron sleepers. Further running tests were carried out involving a real single bogie falling onto ballast or a concrete sleeper. These experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Derailment kinetic energy is proportional to the square of the derailment speed, so even a small increase in derailment speed can have a huge impact on the post-derailment lateral and longitudinal motion of the vehicle. Reducing the derailment speed has a very positive effect on decreasing the post-derailment distance and severity of the derailment accident, as verified by both numerical simulation [10,11] and test [12,13]. However, different derailment speeds can cause the railway component to play different roles in post-derailment behaviour, as revealed by a fullscale derailment test [13].…”
Section: The Main Influential Factorsmentioning
confidence: 75%
See 1 more Smart Citation
“…Derailment kinetic energy is proportional to the square of the derailment speed, so even a small increase in derailment speed can have a huge impact on the post-derailment lateral and longitudinal motion of the vehicle. Reducing the derailment speed has a very positive effect on decreasing the post-derailment distance and severity of the derailment accident, as verified by both numerical simulation [10,11] and test [12,13]. However, different derailment speeds can cause the railway component to play different roles in post-derailment behaviour, as revealed by a fullscale derailment test [13].…”
Section: The Main Influential Factorsmentioning
confidence: 75%
“…The cause of the derailment can be one of the reasons for explaining this phenomenon. A report [10] found that some types of derailments, such as track buckle, defective switches, collision, and overspeed, may escalate quickly, while other types of derailments, including broken wheels, wheel climb, bogie defects, etc., escalate slowly. It is evident that the cause of a derailment can be a significant factor that influences the behaviour of rolling stock after the incident.…”
Section: The Main Influential Factorsmentioning
confidence: 99%
“…While experiments have been conducted using scale models to reproduce vehicle derailment, it is difficult to reproduce these events identically. As such numerical simulations have been conducted in parallel with experiments [9]. Detailed research has thus been carried out into the derailment behavior of vehicles in a major earthquake utilizing numerical simulation.…”
Section: Simulation Of Phenomena That Are Difficult To Reproduce In Ementioning
confidence: 99%
“…Under low-speed conditions, the quasi-static model generally is used to study the train-derailment process [2][3][4][5]. Tests can be conducted through the derailer, and the simulation method is used to analyze the running attitude of the train during derailment [6,7]. The theoretical system of the lateral motion stability of vehicles at low speed is relatively perfect, but there are still many unsolved problems of high-speed derailment.…”
Section: Introductionmentioning
confidence: 99%